KOMUNIKASI POLITIK KEAGAMAAN DALAM MEDIA DIGITAL: STUDI PUSTAKA TENTANG NARASI ISLAM DALAM KONTESTASI WACANA PUBLIK - Sulaiman, Anton (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The transformation of the digital media landscape has fundamentally shifted patterns of religious-based political communication in Indonesia. This phenomenon demands serious academic attention, as Islamic narratives are frequently employed as strategic instruments in contestations over public discourse. This study aims to examine in depth how Islamic narratives are constructed, disseminated, and contested in digital spaces within the context of contemporary Indonesian political communication. The research employs a systematic literature review of scientific sources comprising books published in the last five years and articles from accredited national and internationally reputable journals published in the last three years. The findings reveal that religious political communication in the digital domain is multidimensional, encompassing the use of social media platforms as arenas of opinion formation, selective Islamic framing practices for electoral purposes, and dynamic interactions between state actors, religious figures, and civil society in producing and responding to Islamic narratives. The study also finds that polarization of religious discourse is amplified by digital platform algorithms that create echo chambers, thereby narrowing the space for cross-perspective dialogue. This research underscores the importance of religious digital literacy as a response to the fragmentation of Islamic discourse in the digital public sphere